Ethical observations about the production and marketing of genetically modified vegetal and animal organisms - Bompiani, A. (Medicina e Morale, 2000)
The Author examines the ethical aspects of intense debate which is tacking place on biotechnologies, with special reference to genetically modified organisms. He inquiries into the present role of biotechnologies for human progress, emphasizing the legitimacy of living nature manipulation according to a moderate anthropocentric vision, and stressing the need for defence of environmental biodiversity and a sufficient level of animal welfare. The article also deals with the problems of "risks" which represents one of the most diffused issue within public opinion. It is necessary to acknowledge our present difficulties in offering a precise epidemiological evaluation of the "risks" four human health which derive from the use of genetically modified food present on the market. As a consequence, the following requirements, the article concludes, must be pointed out: 1. Promotion of information about complex questions of biotechnology and genetically modified organisms; 2. Support the criterion of the scientific evaluation of risks, also following the "caution principle" (which indeed should be juridically better defined in regard to biotechnological applications); 3. Arrangements for the development of good relations among the different field involved in biotechnologies (producers, universities that offer research and education activities, consumers, etc.), also with the contribution of criteria such the greatest "transparency" and choice right; 4. Certainty of benefits - which may come from biotechnological applications - for all the people on earth.